2019
DOI: 10.4064/cm7560-8-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hom-groups, representations and homological algebra

Abstract: A Hom-group G is a nonassociative version of a group where associativity, invertibility, and unitality are twisted by a map α : G −→ G. Introducing the Hom-group algebra KG, we observe that Hom-groups are providing examples of Homalgebras, Hom-Lie algebras and Hom-Hopf algebras. We introduce two types of modules over a Hom-group G. To find out more about these modules, we introduce Hom-group (co)homology with coefficients in these modules. Our (co)homology theories generalizes group (co)homologies for groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Throughout this paper, we consider regular Hom-groups that is the case when the structure map is invertible, and this notion can be traced back to Caenepeel and Goyvaerts's pioneering work [3]. The axioms in the following definition of Hom-group is different from the one in [7,8,13]. However, we show that if the structure map is invertible, then some axioms in the original definition are redundant and can be obtained from the Hom-associativity condition.…”
Section: Hom-groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this paper, we consider regular Hom-groups that is the case when the structure map is invertible, and this notion can be traced back to Caenepeel and Goyvaerts's pioneering work [3]. The axioms in the following definition of Hom-group is different from the one in [7,8,13]. However, we show that if the structure map is invertible, then some axioms in the original definition are redundant and can be obtained from the Hom-associativity condition.…”
Section: Hom-groupsmentioning
confidence: 99%
“…He also proved Lagrange's theorem for finite Hom-groups in [8]. The recent developments on Hom-groups (see [7,8,13]) make it natural to study Hom-Lie groups and to explore the relationship between Hom-Lie groups and Hom-Lie algebras.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can associate a Hom-group to any Hom-Lie algebra by considering group-like elements in its universal enveloping algebra. Recently, M. Hassanzadeh developed representations and a (co)homology theory for Hom-groups in [7]. He also proved Lagrange's theorem for finite Hom-groups in [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that a Homassociative algebra gives rise to a Hom-Lie algebra using the commutator. Since then, various Hom-analogues of some classical algebraic structures have been introduced and studied intensively, such as Hom-coalgebras, Hom-bialgebras and Hom-Hopf algebras [24,25], Hom-groups [26,27], Hom-Hopf modules [28], Hom-Lie superalgebras [29,30], generalize Hom-Lie algebras [31], and Hom-Poisson algebras [32].…”
Section: Introductionmentioning
confidence: 99%